SISTEM INFORMASI PEMBERITAHUAN EVENT BERBASIS FRAMEWORK CODE IGNITER - Muhammad Saleh; Irwan Adi Pribadi; Yohana Tri Utami (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Data Management System of Event Organizer for notification of an event to the community based on the Igniter Framework code is done by utilizing the social media features. These data are stored in the form of recorded documents. This research seeks to build an event information system so that data management is easier so information access is faster. This system was developed by the waterfall method. Evaluation of the system in the aspect of appearance by the user shows the value which states that most people want this system to be made so that the community and event organizers are helped a lot. Software test results show that the functions of the Event Organizer Information System For Notification of an Event have been running well according to requirements. The conclusion is that this system is appropriate to be used to assist the work of organizers, event organizers, and users in holding events, finding events, and successfully organizing events.